Protective role of rutin dietary supplementation mediated by purinergic signaling in spleen of silver catfish Rhamdia quelen exposed to organophosphate pesticide trichlorfon - Baldissera M.D. (2021)
© 2021 Elsevier Inc.Evidence suggests the involvement of purinergic signaling, a mechanism mediated by extracellular nucleotides and nucleosides, with the impairment of immune and inflammatory responses in silver catfish (Rhamdia quelen) exposed to trichlorfon. Plant-derived substances have been considered potent anti-inflammatory agents due to effects on the purinergic system, such as the use of the flavonoid rutin. The aim of this study was to determine whether a diet containing rutin is able to prevent or reduce trichlorfon-induced impairment of immune responses through alteration of the purinergic pathway. Spleen adenosine triphosphate (ATP) levels were significantly higher in silver catfish exposed to 11 mg/L trichlorfon for 48 h compared to the control group, while adenosine (Ado) levels were significantly lower. Spleen ectonucleoside triphosphate diphosphohydrolase (NTPDase) activity was significantly lower in silver catfish exposed to trichlorfon compared to control group, while adenosine deaminase activity was significantly higher. Spleen metabolites of nitric oxide, interleukin-1, and IL-6 were significantly higher in silver catfish exposed to trichlorfon compared to control group. Diet with 3 mg rutin/kg diet was able to prevent all the alterations elicited by trichlorfon, except restoring spleen ATP levels. The purinergic exposure signaling is involved in impairment of immune and inflammatory responses in fish exposed to trichlorfon due to reduction in ATP hydrolyses and by an increase in Ado deamination, leading to release of pro-inflammatory mediators. Use of rutin-added diet exerted an essential role in protecting the silver catfish spleen from trichlorfon-induced impairment on immune and inflammatory responses, preventing all alterations on splenic purinergic signaling.